Exploding The Creativity Myth : the Computational Foundations of Linguistic Creativity. - Veale, Tony, 1967- (Bloomsbury Publishing, 2012)
Karl Lagerfeld's description of his sunglasses as a 'Burqa for my eyes' drew a huge amount of commentary. But what was going on within that phrase? Why was it deemed original and contentious and what can it tell us about creativity? Taking us through cliché, metaphor, analogy, neologism and surrealism, amongst other creative tropes, Tony Veale offers a comprehensive guide to the actual processes behind linguistic creativity. By grounding his approachable examples in easy to replicate methods, the book is perfect as a resource for individual creative exploration. Anyone with an open mind and a.